Comparative analysis of the transcriptomes of two rice subspecies during domestication - Hongbo Pang (Nature Portfolio, 2021)
Abstract Two subspecies of rice, Oryza sativa ssp. indica and O. sativa ssp. japonica, with reproductive isolation and differences in morphology and phenotypic differences, were established during the process of rice domestication. To understand how domestication has changed the transcriptomes of the two rice subspecies and given rise to the phenotypic differences, we obtained approximately 700 Gb RNA-Seq data from 26 indica and 25 japonica accessions, and identified 97,005 transcribed fragments and 4579 novel transcriptionally active regions. The two rice subspecies had significantly different gene expression profiles, we identified 1,357 (3.3% in all genes) differentially expressed genes (DEGs) between indica and japonica rice. Combining existing gene function studies, it is found that some of these differential genes are related to the differentiation of the two subspecies, such as grain shape and cold tolerance, etc. Functional annotation of these DEGs indicates that they are involved in cell wall biosynthesis and reproductive processes. Furthermore, compared with the non-DEGs, the DEGs from both subspecies had more 5′flanking regions with low polymorphism to divergence ratios, indicating a stronger positive selection pressure on the regulation of the DEGs. This study improves our understanding of the rice genome by comparatively analyzing the transcriptomes of indica and japonica rice and identifies DEGs those may be responsible for the reproductive isolation and phenotypic differences between the two rice subspecies.